Inclusive innovation and policies to promote inclusive innovation in China and implications for Vietnam - Ta Doan Hai (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
Over the past decades, China has achieved rapid development based on science and technology (S&T). However, this rapid growth model based on S&T also lead to serious consequences such as inequality, wealth gap between rich and poor, and depletion of natural resources. To cope with emerging challenges and achieve the goal of sustainable development, in addition to restructuring production industries China also pursued the policy of building a harmoniously developed society. And with the favorable socio-economic context based on S&T, China has successfully implemented various programs and initiatives with the content and characteristics of inclusive innovation covering a wide scope and scale of implementation. Currently, China is also facing a lot of difficulties and challenges and with many choices in formulating inclusive innovation policies such as building a comprehensive strategy and policy on inclusive innovation, and continuously refining and improving specific inclusive innovation policy mechanisms, based on a deeper understanding of the needs of excluded groups. Despite of the challenges, the successes in inclusive growth that have been achieved in China during long period of time and the policy challenges in implementing inclusive innovation that China is facing will suggest many lessons for developing countries including Vietnam for reference and learning when formulating innovation policies for inclusive growth, ensuring that no one is left behind. Code: 23110801